Ancient masonry arches and vaults strengthened with TRM, SRG and FRP composites: Numerical analyses. (1st March 2018) - Bertolesi, Elisa; Milani, Gabriele; Carozzi, Francesca Giulia; Poggi, Carlo
Abstract: The two arches and the three vaults experimentally described in Carozzi et al. (2017) are here analyzed with a novel robust FE lower bound limit analysis code, suitable to predict active failure mechanisms, lines of thrust and collapse loads in absence and presence of TRM, SRG and FRP reinforcement. The approach relies into a discretization into rigid-infinitely resistant quadrilateral elements for masonry, interfaces between contiguous elements exhibiting limited strength and perfectly bonded rigid-plastic trusses representing the reinforcement. For masonry, a No Tension Material NTM model can be adopted to compare with classic Heyman's results, but also a limited compressive and tensile strength with a cohesive frictional behavior in shear may be accounted for in a relatively simple fashion, i.e. in principle with the possibility to model shear sliding and compression crushing. Debonding and delamination of the reinforcement are considered in a conventional way, assuming trusses with a limited tensile strength derived from either experimental data available or consolidated formulas from the literature. With the knowledge of the exact position of the hinges provided by limit analysis, 2D FE static analyses with non-linearity and softening concentrated exclusively on hinges are carried out, to simply extend the knowledge beyond collapse loads estimation towards a prediction of initial stiffness and ultimate displacements. In all cases, promising agreement with experiments is observed.